A STUDY ON THE PROBLEMS FACED BY THE UNORGANISED RETAILERS IN KERALA - V. M Purushothaman
This research articles has analyzed the problems faced by the unorganized retail traders in Kerala by the large scale entry of organized retailers. The entry of organized retail sector in the Kerala market has created enormous amount of anxieties and apprehensions in the mind of traditional retailers, venders, consumers, political parties and the general public at large. There are five types of problems that are faced by the unorganized retailers by the entry of organized retailers. These include infrastructure problems, product related problems, price related problems, promotion related problems and operation related problems. Of which price related problems are the most prominent problem and that alone contribute 70 percent of the overall problems. The study proved that the existence of unorganized retailers in Kerala is challenging and they face severe competition from the organized retailers and they will be compelled to close down their outlets in the near future.